Women require routine opioids to prevent painful colonoscopies: a randomised controlled trial. (2nd December 2021) - Schult, Anna Lisa; Botteri, Edoardo; Hoff, Geir; Holme, Øyvind; Bretthauer, Michael; Randel, Kristin Ranheim; Gulichsen, Elisabeth Haagensen; El-Safadi, Badboni; Barua, Ishita; Munck, Carl; Nilsen, Linn Rosén; Svendsen, Hege Marie; et al.
Abstract: Background: Women are at high risk for painful colonoscopy. Pain, but also sedation, are barriers to colorectal cancer (CRC) screening participation. In a randomised controlled trial, we compared on-demand with pre-colonoscopy opioid administration to control pain in women at CRC screening age. Methods: Women, aged 55–79 years, attending colonoscopy at two Norwegian endoscopy units were randomised 1:1:1 to (1) fentanyl on-demand, (2) fentanyl prior to colonoscopy, or (3) alfentanil on-demand. The primary endpoint was procedural pain reported by the patients on a validated four-point Likert scale and further dichotomized for the study into painful (moderate or severe pain) and non-painful (slight or no pain) colonoscopy. Secondary endpoints were: willingness to repeat colonoscopy, adverse events, cecal intubation time and rate, and post-procedure recovery time. Results: Between June 2017 and May 2020, 183 patients were included in intention-to-treat analyses in the fentanyl on-demand group, 177 in the fentanyl prior to colonoscopy group, and 179 in the alfentanil on-demand group. Fewer women receiving fentanyl prior to colonoscopy reported a painful colonoscopy compared to those who were given fentanyl on-demand (25.2% vs. 44.1%, p  < .001). There was no difference in the proportion of painful colonoscopies between fentanyl on-demand and alfentanil on-demand (44.1% vs. 39.5%, p  = .40). No differences were observed for adverse events or any of the other secondary endpoints between the three groups. Conclusions: Fentanyl prior to colonoscopy provided better pain control than fentanyl or alfentanil on-demand. Fentanyl before colonoscopy should be recommended to all women at screening age. Trial registration: Clinicaltrials.gov (NCT 01538550). Norwegian Medicines Agency (16/16266-13). EU Clinical Trials Register (EUDRACTNR. 2016-005090-13)